The Effect of Resilience on Students' Mathematics Concept Understanding - Nabilah Firdayanti; Ikhbal Saputra; Maharani Maharani (P3M IAI Nusantara Batang Hari, 2024)
This study aims to find out about the effect of resilience on students' understanding of mathematical concepts. The research method used for this study was survey research at SMP TRAMPIL in 2020 – 2021. The sample used was 30 students consisting of class VIII with the data collection technique using simple random sampling. Data collection was carried out using questionnaires and test questions. The data analysis technique used is descriptive data analysis technique, normality test, linearity test, simple correlation test, coefficient of determination, correlation significance test, regression equation test, and regression significance test. This research was conducted in April – July 2021. The results of the research revealed that: There is a significant influence between resilience and adversity on students' understanding of mathematical concepts by 21.62%. This situation shows that students' understanding of mathematical concepts is contributed by resilience to adversity. Keywords: Effect, Students, Mathematics